ANGUISH IN ALEXANDER DUMAS’ NOVEL THE COUNT OF MONTE CRISTO - Hidayati Hidayati; Arifuddin Arifuddin; Zainab M Z.; Aflina Aflina (Universitas Islam Sumatera Utara (UISU), 2019)
The research is conducted based on the novel The Count of Monte Cristo, written by a French writer Alexander Dumas. The focus goes to anguish experienced by the protagonist of the novel, Edmond Dante, a young and handsome sailor with a brilliant prospects in career making him plunged into life of anguish. He is arrested for no reason, sent to jail with inhuman treatment. Descriptive qualitative method is applied to reveal that literary works are mirrors of all the occurrences in society. This is in line with the sociology of literature also implemented here as the approach to further analysis of the subject matters having three aspects to be used as a literary research guidelines: social contexts of the author, already showed by the author, literature as the reflection of society, revealed through the text tending to social reality and functions of literature as entertainer or remodel of society, exposed through the responses of the readers. The results show that the novel contains anguish subdivided into Non-procedural Arrest and Inhuman Imprisonment covering the whole study.